Different time course recovery of muscle oedema within the quadriceps femoris and functional performance after single- vs multi-joint exercises - Dourado, Marco; Vieira, Denis; Boullosa, Daniel; Bottaro, Martim (Biology of Sport, 2023)
This study aimed to verify the time course recovery of muscle edema within the quadriceps femoris and functional performance after lower-body single- and multi-joint exercises. For this within-participant unilateral and contralateral experimental design, fourteen untrained young males performed a unilateral knee extension exercise (KE), and a unilateral leg press (LP) exercise in a counterbalanced order. At pre-, post-, 24 h, 48 h, 72 h, and 96 h after exercise, the peak torque (PT), unilateral countermovement jump (uCMJ) performance, and rectus femoris (RF) and vastus lateralis (VL) muscle thicknesses were recorded in both legs. The PT decreased immediately after (p = 0.01) both exercises (KE and LP) and was fully recovered 24 h after KE (p = 0.38) and 48 h after LP (p = 0.68). Jump height and power, in the uCMJ, followed the same PT recovery pattern after both exercises. However, vertical stiffness (Kvert) was not affected at any time point after both protocols. The RF thickness increased after both exercises (p = 0.01) and was fully restored 48 h after KE (p = 0.86) and 96 h after LP (p = 1.00). The VL thickness increased after both exercises (p = 0.01) and was fully restored 24 h after LP (p = 1.00) and 48 h after KE (p = 1.00). The LP exercise, compared to KE, induced more prolonged impairment of functional performance and delayed recovery of RF muscle edema. However, the VL edemainduced muscle swelling recovery was delayed after the KE exercise. The different recovery kinetics between functional performance and muscle damage should be taken into consideration depending on the objectives of the next training sessions.